PROFILE OF ALLERGY HYPERPLASMA PATHOLOGIC ANTIBODY AND IMMUNOGENIC CHARACTERISTIC - Nazaruddin Nazaruddin; Hamdani Budiman; Basri A. Gani; Subhaini Jakfar; M. Hasan; Muhammad Hanafiah (Jurnal Kedokteran Hewan, 2017)
The objective of this research was to determine the allergy hyperplasma pathologic antibody and to evaluate the immunogenic characteristics. Blood and serum were collected from human suffering rhinitis, skin, eye and asthma allergies. To obtain a cloned allergen plasma protein (protein allergen that had been induced with the serum from human with allergic rhinitis, skin, eye and asthma), the goat was used as an intermediate animal. Hematological analysis showed that the leukocyte cell such as neutrophil, lymphocyte, monocyte, and eosinophil increase in allergic-suffered human. The blood smear test exhibited that the mastocyte cell was dominant which contributes to allergy activities in human body. The sodium dodecyl sulphate-polyacrylimide gel electrophoresis (SDS-PAGE) assay detected protein allergens with molecular weight of 188 kDa (IgE) and 60-62 kDa (mastocyte cell). The reactivity assay using enzyme linked immunosorbent-assay (ELISA) revealed that cloned-allergens (whole hyperplasma allergen from goat isolates) express the best reactivity at various concentrations of IgE than the leukocyte cells. This research concluded that the clones of protein allergen have better immunogenic characteristic and those proteins can be recommended as the candidate of allergen to induce the humoral immunity on host and deliver specific product of anti-allergy such as milk.